2001
DOI: 10.1002/1522-2683(200111)22:19<4139::aid-elps4139>3.0.co;2-g
|View full text |Cite
|
Sign up to set email alerts
|

Recent advances in capillary electrophoresis of peptides

Abstract: The article gives a comprehensive review on the recent developments in the applications of high-performance capillary electromigration methods, including zone electrophoresis, isotachophoresis, isoelectric focusing, affinity electrophoresis, electrokinetic chromatography and electrochromatography, to analysis, preparation and physicochemical characterization of peptides. The article presents new approaches to the theoretical description and experimental verification of electromigration behavior of peptides, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
52
0

Year Published

2001
2001
2005
2005

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 99 publications
(52 citation statements)
references
References 238 publications
(196 reference statements)
0
52
0
Order By: Relevance
“…Separation of peptides by capillary electrophoresis (CE) has become one of the most important application fields of this technique [1][2][3][4][5][6]. By using CE it has been possible to obtain valuable information on identity, purity and structural changes of peptides [7][8][9][10].…”
Section: Introductionmentioning
confidence: 79%
“…Separation of peptides by capillary electrophoresis (CE) has become one of the most important application fields of this technique [1][2][3][4][5][6]. By using CE it has been possible to obtain valuable information on identity, purity and structural changes of peptides [7][8][9][10].…”
Section: Introductionmentioning
confidence: 79%
“…Most current CZE applications for peptides have involved relatively simple model mixtures or enzymatic digests of individual proteins [16,19]. Our previous comparison between CZE and gradient capillary reversed-phase liquid chromatography (RPLC) in the separation of tryptic digests of yeast lysate showed that CZE yielded a lower resolution than the RPLC approach [37].…”
Section: Czementioning
confidence: 99%
“…Most CIEF peaks in Fig. 3, including the narrowest peaks (peaks [16][17][18][19][20][21][22], are reproducibly observed. For other peaks (e.g., peaks 10-12 and 15), some minor differences in peak resolution and intensity are evident.…”
Section: Cief Of Protein Complexesmentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3][4][5][6][7][8][9][10][11][12][13][14] By building on these and earlier efforts, it is anticipated that the popularity of CE-MS will grow, and its advantages will be better appreciated and exploited.…”
Section: Introductionmentioning
confidence: 99%